Cycle time and idle time analysis of draglines for increased productivity - A case study - Rai P.; Trivedi R.; Nath R. (My University, 2025)
In India, massive opencast mines are being planned, with dragline as an excavator, to strip out large volumes of overburden (O/B) at a high stripping ratio. The increased use of draglines is primarily because the draglines have tremendous flexibility of operation at varying O/B depths. Besides, it is capable of giving higher rate of O/B removal at relatively low operating cost. However, at the same time, it must be distinctly borne in mind that the dragline is single most expensive equipment to be procured by a mine. Hence, analysis of cycle time and idle time is of tremendous significance with such capital intensive equipment. Such analysis paves the way for improvement in the utilization, production and productivity of this equipment. The present study is based on field investigation conducted on draglines in one of the most prestigious opencast coal mines of Coal India Limited. The study critically analyses the cycle time and the idle time distribution of the draglines, as operating in the field.